2021
DOI: 10.1177/00236772211025166
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of laboratory animal professionals and researchers towards carbon dioxide euthanasia for rodents and perceived barriers to change

Abstract: Evidence indicates that carbon dioxide (CO2) induces negative affective states (including anxiety, fear and distress) in laboratory rodents, but many countries still accept it for euthanasia. Alternative methods (e.g. inhalant anaesthetic) may represent a refinement over CO2 but are not widely adopted. We conducted an online survey of Canadian and European laboratory animal professionals and researchers ( n = 592) to assess their attitudes towards the use of CO2 and alternative methods for rodent euthanasia us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Overall, we found that the most widely preferred killing method for rodents was cervical dislocation and not CO 2 as reported by a recent survey 20 . This method involves the separation of the cervical vertebrae resulting in lethal trauma to the spinal cord and is commonly performed by placing the finger (manual) or an instrument (mechanical) behind the base of the skull whilst pulling the tail firmly to achieve rapid separation of the high cervical vertebrae.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Overall, we found that the most widely preferred killing method for rodents was cervical dislocation and not CO 2 as reported by a recent survey 20 . This method involves the separation of the cervical vertebrae resulting in lethal trauma to the spinal cord and is commonly performed by placing the finger (manual) or an instrument (mechanical) behind the base of the skull whilst pulling the tail firmly to achieve rapid separation of the high cervical vertebrae.…”
Section: Discussionsupporting
confidence: 66%
“…Two previous studies have obtained responses from laboratory personnel regarding killing practices. However, one was focused on the consequences of killing on human quality of life rather than animal welfare consequences 19 , and the other solely focused on attitudes towards CO 2 killing with no focus on procedural aspects or other permitted methods 20 . Despite four methods being permitted for use in Schedule 1 ASPA legislation, we found that only 10% of respondents had all four methods available for use for killing adult laboratory rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Animal care staff in one study reported a slight increase in workload when shelters and nesting material were introduced in their animal units, but their overall impression of the enrichment was positive [ 100 ]. Lack of time has also been identified as a major barrier to the adoption of non-aversive handling methods for laboratory mice [ 101 ] and refined euthanasia methods [ 102 ]. Likewise, in the zoo community, technicians often feel constrained by lack of time [ 103 ] or lack of institutional support rather than lack of personal motivation to implement enrichment [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to carbon dioxide (CO 2 ) gas in a rising concentration is favoured for killing laboratory rodents because of its capacity for high-throughput and non-contact nature [ 2 ]. However, there are significant welfare concerns surrounding its use, and several studies dispute its ability to provide a humane death [ 3 ].…”
Section: Introductionmentioning
confidence: 99%